RECONSTRUCTION OF MAXIMUM GLACIAL EXTENT IN THE CENTRAL SØR RONDANE MOUNTAINS, EAST ANTARCTICA - ヒラカワ, カズオミ; マツオカ, ノリカズ; モリワキ, キイチ; HIRAKAWA, Kazuomi; MATSUOKA, Norikazu; MORIWAKI, Kiichi (National Institute of Polar Research, 1988)
P(論文) Glacial landforms and deposits indicating the past expansion of glaciers are described. It is conspicuous that thick erratics form an end-moraine ridge or an extensive depositional surface on the summit, and that roches moutonnees are developed on the sharp ridge. On the basis of these traces, a paleogeographical reconstruction during the time of the maximum glaciation is presented : (1) The southern half of the central Sør Rondane Mountains was mostly covered with the ice sheet from the ice plateau; (2) Ice fall was located 10km further north than at present; (3) Ice was about 300-350m thicker than at present; (4) The northern half of the central Sør Rondane Mountains rose relatively widely above the ice sheet and outlet glacier. departmental bulletin paper